2019
DOI: 10.1186/s13287-019-1307-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell repression of Th17 cells is triggered by mitochondrial transfer

Abstract: Background Mesenchymal stem cells (MSCs) are multipotent cells with broad immunosuppressive capacities. Recently, it has been reported that MSCs can transfer mitochondria to various cell types, including fibroblast, cancer, and endothelial cells. It has been suggested that mitochondrial transfer is associated with a physiological response to cues released by damaged cells to restore and regenerate damaged tissue. However, the role of mitochondrial transfer to immune competent cells has been poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 34 publications
5
70
1
Order By: Relevance
“…MSCs have also been reported to transfer mitochondria to immune cells including T cells and macrophages. In these settings, transferred mitochondria decreased inflammation by promoting recipient immune cell differentiation towards an anti-inflammatory phenotype [ 111 , 112 , 113 , 114 , 115 , 116 ]. On the contrary, the transfer to T cells of mitochondria originating from myeloid cells was shown to exacerbate inflammation and to lead to asthma aggravation [ 117 ].…”
Section: Mitochondria As Signaling Organelles: Functional Effectsmentioning
confidence: 99%
“…MSCs have also been reported to transfer mitochondria to immune cells including T cells and macrophages. In these settings, transferred mitochondria decreased inflammation by promoting recipient immune cell differentiation towards an anti-inflammatory phenotype [ 111 , 112 , 113 , 114 , 115 , 116 ]. On the contrary, the transfer to T cells of mitochondria originating from myeloid cells was shown to exacerbate inflammation and to lead to asthma aggravation [ 117 ].…”
Section: Mitochondria As Signaling Organelles: Functional Effectsmentioning
confidence: 99%
“…Thus, these results suggest that the immunoregulatory potential of MSC involves other metabolic pathways than those related to PPARβ/δ. Indeed, recently it has been demonstrated that mitochondrial transfer from MSC to T cells represents a novel mechanism of immunosuppression involved in the inhibition of Th17 cell proliferation and function as well as in the generation of regulatory T cells to restrain inflammation 13,14 . Thus, the improved immunosuppressive activity of MSC PPARβ/δ −/− could be associated to their higher mitochondrial transfer capacity as compared to MSC PPARβ/δ +/+ .…”
Section: Discussionmentioning
confidence: 99%
“…Luz-Crawford et al reported that coculturing healthy donor-derived BMSCs with Th17 effector cells leads to mitochondrial transfer, which increases respiration in recipient Th17 cells and reprograms the energetic metabolism from glycolysis to OXPHOS; this change is associated with a reduced production of IL-17 and suppresses proinflammatory functions of Th17 effector cells. Interestingly, coculture with rheumatoid arthritis patient-derived BMSCs showed that mitochondrial transfer is impaired compared with that with healthy donor-derived BMSCs, suggesting that resident tissue MSCs may represent a regulatory niche to balance the proinflammatory and anti-inflammatory responses; and part of the regulatory mechanisms may be mediated by mitochondrial transfer from MSCs [ 38 ]. Similarly, a study from Court et al demonstrated that mitochondrial transfer facilitates Treg differentiation through the enhanced expression of mRNA transcripts such as FOXP3, IL2RA, CTLA4, and TGFb1, which are involved in Treg cell differentiation [ 39 ].…”
Section: Mitochondrial Transfer Impacts Cellular Metabolism and Inmentioning
confidence: 99%